Newborn Screening for X-Linked Adrenoleukodystrophy: Review of Data and Outcomes in Pennsylvania - Jessica R. C. Priestley; Laura A. Adang; Sarah Drewes Williams; Uta Lichter-Konecki; Caitlin Menello; Nicole M. Engelhardt; James C. DiPerna; Brenda DiBoscio; Rebecca C. Ahrens-Nicklas; Andrew C. Edmondson; Francis Jeshira Reynoso Santos; Can Ficicioglu (MDPI AG, 2022)
X-linked adrenoleukodystrophy (X-ALD) is the most common peroxisomal disorder. It results from pathogenic variants in ABCD1, which encodes the peroxisomal very-long-chain fatty acid transporter, causing a spectrum of neurodegenerative phenotypes. The childhood cerebral form of the disease is particularly devastating. Early diagnosis and intervention improve outcomes. Because newborn screening facilitates identification of at-risk individuals during their asymptomatic period, X-ALD was added to the Pennsylvania newborn screening program in 2017. We analyzed outcomes from the first four years of X-ALD newborn screening, which employed a two-tier approach and reflexive ABCD1 sequencing. There were 51 positive screens with elevated C26:0-lysophosphatidylcholine on second-tier screening. ABCD1 sequencing identified 21 hemizygous males and 24 heterozygous females, and clinical follow up identified four patients with peroxisomal biogenesis disorders. There were two false-positive cases and one false-negative case. Three unscreened individuals, two of whom were symptomatic, were diagnosed following their young siblings' newborn screening results. Combined with experiences from six other states, this suggests a U.S. incidence of roughly 1 in 10,500, higher than had been previously reported. Many of these infants lack a known family history of X-ALD. Together, these data highlight both the achievements and challenges of newborn screening for X-ALD.